Dissenting Opinion Hakim Pengadilan Agama Tanjung Karang Pada Perkara Hak Asuh Anak Bagi Ibu Yang Murtad - Agustin, Cleo Nadia; Murdiana, Elfa; Setiawan, Wahyu; Manasikana, Adellia; Nurli Darmawati, Sifa (Institut Agama Islam Negeri Kendari, 2025)
This study examines the dissenting opinion in a child custody case following apostasy at the Tanjung Karang Religious Court, Class 1A, as a reflection of the dynamic interplay between Islamic family law, substantive justice, and child protection principles. The main research problem concerns how the judges’ legal reasoning patterns are formed within this context of differing opinions and to what extent the dissenting opinion contributes to reinforcing the principles of maslahah mursalah, maqasid al-shari‘ah, and the best interest of the child. Employing a qualitative methodology with a juridical-empirical approach, this study adopts a case study design on Decision No. 948/Pdt.G/2023/PA.Tnk, supported by in-depth interviews with the presiding judges and comparative analysis of national and international jurisprudence. The findings reveal two dominant paradigms in judicial reasoning: the normative-formalistic paradigm, which emphasizes hifz al-dīn (protection of religion), and the substantive-contextual paradigm, which prioritizes the child’s welfare as the core orientation of justice. The dissenting opinion functions as a form of rechtsvinding (judicial legal discovery), bridging textual legal interpretation and social realities to achieve more humanistic justice. This study recommends further comparative research across Muslim-majority countries such as Malaysia, Egypt, and Morocco to enrich the global discourse on Islamic law that is adaptive and responsive to the best interests of the child.